Sent Out of the Garden: Posthuman Stewardship in Margaret Atwood’s MaddAddam Trilogy - Sebastian, Alphy (Literary Studies, 2024)
The theme of bequeathing the human agency upon the ecosystem to post-human embodiments in literature is triggered by the wilful neglect of environmental hazards on the part of humanity in favour of capitalist concerns. The grave ecological concerns haunting the contemporary world culminated in the replacement of human stewardship to genetically modified, Crakers, in the MaddAddam trilogy by Atwood. Replete with biblical imagery, the new gardeners in the novel, are expected to salvage the sterile wasteland left by human civilization and transform it into a thriving Eden once again. MaddAddam Trilogy features a “fictional catastrophe” (285) written by a deeply unsettled Atwood while she was witnessing the receding glaciers on a boat in the Arctic. Although critics such as Marlene Holm and Bouson accuse Atwood privileging of humanist values and human traits at the cost of mocking “the idea of a bioengineered posthuman future” (Bouson 149) at all levels of the trilogy, introducing a new subjectivity to the otherwise anthropocentric vision of society remains significant. In this paper, my primary aim is to study the nature of posthuman embodiment conceptualized by Atwood as the better custodians of nature. Do posthuman hybrids signify a utopian fantasy of human improvement or a radical reconfiguration of human subjectivity?